Nowhere to go? Surveillance, privacy rules and trade talks - Roderick Abbott; Hosuk Lee-Makiyama (European Centre for International Political Economy (ECIPE), 2014)
This policy brief outlines the chronology of the developments since Edward Snowden leaked the documents on large-scale electronic surveillance, including PRISM and Tempora programmes, the policy implications and the public's response. It concludes that the nature of the debate has shifted from a legal and constitutional issue about US surveillance, to a global concern. The revelations have led to divergent attitudes towards surveillance operations, with Britain and other Anglophone countries on one side, and others in Europe and Brazil and in Asia judging intelligence activity more critically (but at times disingenuously). There is also a growing opposition from telecom companies and Internet providers in the US to being forced to pass on the personal data collected during their commercial operations to the government. At this stage, the gulf between security needs and the privacy rights of individuals, both Americans and others, is as wide as ever. However, European attempts to promote data privacy rules as a safeguard against electronic surveillance proved to be unsuccessful, as the rules were not designed for that purpose and comes at disproportionately high costs. So were attempts to leverage on TTIP negotiations, especially as Europe is the demandeur of that FTA - not the US. Data privacy rules are also regulatory barriers in the eyes of trade negotiators, proven by the EU's own offensive stance in its prior FTAs.
Keywords: 330; Datenschutz; Informationsfreiheit; Geheimdienst; USA; EU-Staaten